Seminal Microbiota of Idiopathic Infertile Patients and Its Relationship With Sperm DNA Integrity - Garcia-Segura, Sergio; del Rey, Javier; Closa, Laia; Garcia-Martínez, Iris; Hobeich, Carlos; Castel, Ana Belén; Vidal, Francisco; Benet, Jordi; Ribas-Maynou, Jordi; Oliver-Bonet, Maria (Frontiers in Cell and Developmental Biology, 2022)
The development of new biomarkers for human male infertility is crucial to improve the diagnosis and the prognosis of this disease. Recently, seminal microbiota was shown to be related to sperm quality parameters, suggesting an effect in human fertility and postulating it as a biomarker candidate. However, its relationship to sperm DNA integrity has not been studied yet. The aim of the present study is to characterize the seminal microbiota of a western Mediterranean population and to evaluate its relationship to sperm chromatin integrity parameters, and oxidative stress. For that purpose, 14 samples from sperm donors and 42 samples from infertile idiopathic patients were obtained and were analyzed to assess the composition of the microbiota through full-length 16S rRNA gene sequencing (Illumina MiSeq platform). Microbial diversity and relative abundances were compared to classic sperm quality parameters (macroscopic semen parameters, motility, morphology and concentration), chromatin integrity (global DNA damage, double-stranded DNA breaks and DNA protamination status) and oxidative stress levels (oxidation-reduction potential). The seminal microbiota observed of these samples belonged to the phyla Firmicutes, Proteobacteria, Actinobacteria and Bacteroidetes. The most abundant genera were Finegoldia, Peptoniphilus, Anaerococcus, Campylobacter, Streptococcus, Staphylococcus, Moraxella, Prevotella, Ezakiella, Corynebacterium and Lactobacillus. To our knowledge, this is the first detection of Ezakiella genus in seminal samples. Two clusters of microbial profiles were built based on a clustering analysis, and specific genera were found with different frequencies in relation to seminal quality defects. The abundances of several bacteria negatively correlate with the sperm global DNA fragmentation, most notably Moraxella, Brevundimonas and Flavobacterium. The latter two were also associated with higher sperm motility and Brevundimonas additionally with lower oxidative-reduction potential. Actinomycetaceae, Ralstonia and Paenibacillus correlated with reduced chromatin protamination status and increased double-stranded DNA fragmentation. These effects on DNA integrity coincide in many cases with the metabolism or enzymatic activities of these genera. Significant differences between fertile and infertile men were found in the relative presence of the Propionibacteriaceae family and the Cutibacterium, Rhodopseudomonas and Oligotropha genera, which supports its possible involvement in male fertility. Our findings sustain the hypothesis that the seminal microbiome has an effect on male fertility.